An Overview of E-Commerce Practices of Marketing on Supply Chain Management in India: Emerging Business Opportunities and Challenges - Ramesh Chandra Rath; Mrs.Sanghamitra Samal (International Journal of Supply Chain Management, 2013)
Now-a-days, the practice of E-Commercehas been dramatically changed, particularly in last five years .The traditionalway of managing supply has been changed due to wide spread of Global Marketingand supply chain Management. Today a-face -to-face management interactionsystem and the Old traditional form of communication such as letter writing, manualtracking Systems, Paper dominated order processing works and wiredcommunication links were already obsolesce. The primary management system oftools and logistics management department were closed due to its lack of in -efficiencyand efficacy of works in comparison to modern operating systems of marketing.Hence, the invited article, provides an overview regarding the importance ofE-commerce adoption in the present era for the product promotion work made bythe business firms, companies, industries, etc. are succeed in the means ofsupply chain Management and discussed about some of the new tools trendsused for product promotion. It includes website structure, e-purchasing,electronic market place building, for a better promotion work (Business) inIndia by the proper implementation of supply chain management system and how itinfluences the business opportunities for various firms, organizations,industries .Therefore, E-Commerce form of marketing is a process or a moderntechnique used by business firms, companies, and industries for doing theirbusiness work through the e-net system. The authors have done theirextensive research work by taking number of companies of India regarding theirmode of promotion work adopting while they import export of products fromvarious places of India and India abroad, they observed how they followed e-marketingactivities by the help of net-working systems in order to enhancing theirbusiness plans, strategies for better product promotion as well as increasing economicalhealth of various industries, firms, organizations etc.